TINGKAT KECERDASAN SPIRITUAL MAHASISWA DITINJAU DARI KEAKTIFAN DALAM EKSTRAKURIKULER KEAGAMAAN - Khaliq, Restu; Fatimah, Siti; Melati, Melati (Jurnal Studia Insania, 2019)
This study aims to determine whether there are differences in the level of spiritual intelligence of someone who actively participates in religious extracurricular activities LPPQ with those who are not active. This study uses indicators of spiritual intelligence that are not affiliated with Islam, namely the Spiritual Intelligence Self-Report Inventory (SISRI-24), which was initiated by David King. Hypothesis analysis of this study uses the Mann-Whitney U-test. The results showed that there were significant differences between the spiritual intelligence of LPPQ students member and spiritual intelligence of non-LPPQ members with a value of ? = 0,000. Based on the dimensions, there are also significant differences in spiritual intelligence from the critical dimensions of existential thinking, personal meaning production, transcendental consciousness, and consciousness state expansion. The value of ? for each category of spiritual intelligence dimensions is 0.001, 0,000, 0.003 and 0,005 respectively.